Wet oxidation catalyst as well as preparation method and application thereof

By using styrene-based porous microsphere resin to coat the conjugated carbon and perform sulfonation and impregnation of precious metal salts in the wet oxidation catalyst, an efficient wet oxidation catalyst is formed, which solves the problem of low organic pollutant removal rate in the prior art and achieves efficient organic wastewater treatment.

CN119838633AActive Publication Date: 2025-04-18HUNAN INSTITUTE OF ENGINEERING

Patent Information

Application Number
CN202510324505.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

When treating organic pollutants, the existing wet oxidation catalysts have a low removal rate, making it difficult to meet the efficient needs of industrial wastewater treatment.

Method used

Styrene-based porous microsphere resin is used as raw material, and the conjugated carbon organic porous polymer is coated on the surface of the resin through adsorption polymerization, and sulfonation reaction and impregnation of noble metal salt solution is carried out to form a conjugated carbon-coated porous microsphere resin metal composite as a wet oxidation catalyst.

Benefits of technology

The removal rate of organic pollutants has been significantly improved, and the removal rate of bisphenol A has reached more than 95%, which has improved the catalytic oxidation and degradation efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a wet oxidation catalyst as well as a preparation method and application thereof, and belongs to the field of wastewater treatment. Styrene porous microsphere resin is used as a raw material, under the action of a catalyst, polyfunctional aldehyde group small molecules and polyfunctional cyano group small molecules are subjected to a Knoevenagel reaction in an adsorption polymerization mode, the surface of the styrene porous microsphere resin is coated with a layer of conjugated carbon organic porous polymer, and the conjugated carbon organic porous polymer is prepared. Forming conjugated carbon coated porous microsphere resin; then carrying out sulfonation reaction to obtain sulfonic acid group modified conjugated carbon coated porous microsphere resin; and then dipping in a noble metal salt solution to form a resin metal compound, and then filtering, washing and drying to obtain the wet oxidation catalyst. The catalyst can be used for catalytic oxidation degradation of organic wastewater, bisphenol A is used as simulated organic wastewater, and the removal rate of treated bisphenol A is 95% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wastewater treatment, and in particular relates to a wet oxidation catalyst and a preparation method and application thereof. Background Art

[0002] In practical applications, the sewage is pumped into the heat exchanger through a storage tank by a high-pressure pump, and heat is exchanged with the high-temperature oxidation liquid after the reaction, so that the temperature rises to close to the reaction temperature before entering the reactor. The oxygen required for the reaction is pumped into the reactor by a compressor. In the reactor, the organic matter in the sewage reacts with oxygen in an exothermic manner. At a higher temperature, the organic matter in the sewage is oxidized into carbon dioxide and water, or intermediate products such as small molecular organic acids. After the reaction, the gas-liquid mixture is separated by a separator, and the liquid phase is preheated and fed through a heat exchanger to recover heat energy. The high-temperature and high-pressure tail gas first generates steam through a reboiler or preheats the boiler water through a heat exchanger. The condensed water is separated by the separator and then pumped into the reactor through a circulating pump. The separated high-pressure tail gas can generate mechanical energy or electrical energy. The wet catalytic oxidation technology has the advantages of high purification efficiency, less secondary pollution, a wide treatment range, and high economic benefits. It is one of the cutting-edge technologies in the field of difficult-to-degrade industrial wastewater treatment technology.

[0003] At present, wet oxidation catalysts are generally activated carbon and metal oxides, and the use of polymer catalysts in wet oxidation catalysts needs further research. Polymer resin composite modified wet oxidation catalysts have both enrichment and catalytic functions, and have industrial development prospects and application potential. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a wet oxidation catalyst and a preparation method and application thereof, which has a high removal rate of organic pollutants.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a wet oxidation catalyst comprises the following steps: (1) Using styrene-based porous microsphere resin as raw material, multifunctional aldehyde small molecules and multifunctional cyano small molecules undergo Knoevenagel reaction by adsorption polymerization under the action of a catalyst, and a layer of conjugated carbon organic porous polymer is coated on the surface of the styrene-based porous microsphere resin to form a conjugated carbon-coated porous microsphere resin; (2) subjecting the conjugated carbon-coated porous microsphere resin to a sulfonation reaction to obtain a sulfonic acid group-modified conjugated carbon-coated porous microsphere resin; (3) The sulfonic acid group-modified conjugated carbon-coated porous microsphere resin is impregnated in a noble metal salt solution to form a resin-metal complex, which is then filtered, washed, and dried to obtain the wet oxidation catalyst.

[0006] As a further improvement, the multifunctional aldehyde-based small molecule in step (1) is one or any combination of terephthalaldehyde, biphenyldicarboxaldehyde, and trimesaldehyde.

[0007] As a further improvement, the multifunctional cyano small molecule in step (1) is terephthalonitrile and / or biphenyldiacetonitrile.

[0008] As a further improvement, the catalyst in step (1) is tetrabutylammonium hydroxide.

[0009] As a further improvement, the reaction temperature of step (1) is 100-120°C.

[0010] As a further improvement, the noble metal salt in step (3) is one or any combination of ruthenium chloride, iridium chloride, chloroauric acid, and platinum chloride.

[0011] As a further improvement, the amount of the noble metal salt used in step (3) is 1-5% of the mass of the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin.

[0012] As a further improvement, the immersion temperature in step (3) is 60-80°C.

[0013] The present invention provides a wet oxidation catalyst, which is prepared by adopting the method described.

[0014] The present invention also provides an application of the wet oxidation catalyst in degrading organic wastewater.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses styrene porous microsphere resin as raw material, firstly, by means of adsorption polymerization, multifunctional aldehyde small molecules and multifunctional cyano small molecules undergo Knoevenagel reaction to coat a layer of conjugated carbon organic porous polymer on the surface of the porous microsphere resin, to form a conjugated carbon coated porous microsphere resin. Medium polarity and polar resins have good adsorption capacity for organic matter, can enrich organic matter, and increase the contact efficiency between oxidizing species and organic pollutants. Porous conjugated carbon has a graphene-like structure and characteristics, and its introduction can better stimulate hydrogen peroxide to rapidly produce a large number of hydroxyl radicals. Then, the conjugated carbon coated porous microsphere resin is subjected to sulfonation reaction to obtain a sulfonic acid group modified conjugated carbon coated porous microsphere resin, and the introduction of sulfonic acid groups can increase the adsorption sites of precious metals and enhance the loading capacity of precious metals. Then, the sulfonic acid group modified conjugated carbon coated porous microsphere resin is immersed in a precious metal solution to form a resin metal complex, and the introduction of precious metals can further stimulate the activity of hydroxyl radicals and accelerate the oxidative decomposition of organic matter.

[0016] The catalyst is loaded into a high-pressure reactor and can be used for catalytic oxidation degradation of organic wastewater by controlling the temperature and adding an oxidant. Taking bisphenol A as the simulated organic wastewater, the removal rate of bisphenol A after treatment is above 95%. DETAILED DESCRIPTION

[0017] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0018] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0019] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0020] In some embodiments of the present invention, the method for preparing a wet oxidation catalyst comprises the following steps: (1) Using styrene-based porous microsphere resin as raw material, multifunctional aldehyde small molecules and multifunctional cyano small molecules undergo Knoevenagel reaction under the action of a catalyst by adsorption polymerization, and a layer of conjugated carbon organic porous polymer is coated on the surface of the porous microsphere resin to form a conjugated carbon-coated porous microsphere resin.

[0021] In some embodiments, the styrene porous microsphere resin may be a polystyrene porous microsphere resin, which may be polar or medium polar, with a particle size of 0.5-5 mm. It is dried before use at a drying temperature of 80-120°C.

[0022] In some embodiments, the multifunctional aldehyde-based small molecule can be one or more of terephthalaldehyde, biphenyldicarboxaldehyde, and trimesic acid. The amount of the multifunctional aldehyde-based small molecule is 1-5% of the mass of the porous microsphere resin.

[0023] In some embodiments, the multifunctional cyano small molecule can be one of terephthalonitrile and biphenyl diacetonitrile or a mixture of the two. The amount of the multifunctional cyano small molecule is 1-5% of the mass of the porous microsphere resin. In some embodiments, the catalyst used is tetrabutylammonium hydroxide, and the amount of the catalyst used is 0.1-0.5% of the mass of the porous microsphere resin. The reaction solvent is mesitylene, and the amount used is 2-4 times the mass of the porous microsphere resin. The reaction temperature is 100-120° C., and the reaction time is 12-24 hours.

[0024] (2) The conjugated carbon-coated porous microsphere resin is subjected to a sulfonation reaction to obtain a sulfonic acid group-modified conjugated carbon-coated porous microsphere resin.

[0025] In some embodiments, the sulfonation reagent is a sulfuric acid solution with a mass concentration of 30-60%. The sulfonation reaction temperature is 80-100° C. and the sulfonation time is 6-8 hours.

[0026] (3) The sulfonic acid group-modified conjugated carbon-coated porous microsphere resin is impregnated in a noble metal salt solution to form a resin-metal complex, which is then filtered, washed, and dried to obtain the wet oxidation catalyst.

[0027] In some embodiments, the noble metal salt can be one or more of ruthenium chloride, iridium chloride, chloroauric acid, and platinum chloride. The amount of the noble metal salt is 1-5% of the mass of the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin, the mass concentration of the metal salt aqueous solution is 5-10%, the immersion time is 4-8h, and the immersion temperature is 60-80°C.

[0028] In some embodiments, the resin metal complex washing solvents are methanol and toluene in sequence. The vacuum drying temperature of the complex is 80-120° C., and the drying time is 12 hours.

[0029] When in use, the catalyst is directly loaded into the wet oxidation reactor for the treatment of organic wastewater containing bisphenol A, chlorobenzene, nitrobenzene, etc. The oxidant can be hydrogen peroxide, and the amount of hydrogen peroxide added is 0.1~0.2% of the wastewater volume. The wet oxidation temperature is 120-160℃.

[0030] In the wet oxidation catalytic system, hydrogen peroxide will be catalyzed to produce a large number of hydroxyl radicals, which are highly oxidative active species. Hydroxyl radicals first attack the benzene ring structure of bisphenol A to break the bonds of bisphenol A to generate small organic molecules, which are further oxidized by hydroxyl radicals to carbon dioxide and water. If only hydrogen peroxide is added without any catalyst, the degradation rate of bisphenol A is less than 20%.

[0031] In the following embodiments, the medium polar styrene porous microsphere resin adopts the D113 macroporous weakly acidic cation exchange resin produced by Langfang Senate Chemical Co., Ltd., and the polar styrene porous microsphere resin adopts the D001 macroporous strongly acidic cation exchange resin produced by Langfang Senate Chemical Co., Ltd.

[0032] Example 1 1kg of medium polar styrene porous microsphere resin with a particle size of 2mm was placed in a 100℃ blast drying oven for 12h for drying and standby use. 10g of terephthalaldehyde, 15g of terephthalonitrile and 1g of tetrabutylammonium hydroxide were dissolved in 2kg of mesitylene to prepare a solution. The dried resin was poured into the above solution, heated to 120℃ for reaction for 24h, filtered after the reaction to obtain conjugated carbon-coated porous microsphere resin, poured into 50% sulfuric acid solution, heated to 100℃ for reaction for 8h, and filtered to obtain sulfonic acid group-modified conjugated carbon-coated porous microsphere resin. 10g of ruthenium chloride was prepared into a 5% aqueous solution and heated to 60℃, poured the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin into a metal salt solution and soaked for 8h, then filtered off the excess solution and washed with methanol and toluene in turn, and the washed composite was dried at 100℃ for 12h to obtain a wet oxidation catalyst.

[0033] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 1.4mg / L and the removal rate was 98.6%.

[0034] Example 2 1kg of polar styrene porous microsphere resin with a particle size of 2mm was placed in a 100℃ blast drying oven for 12h for drying and standby use. 10g of terephthalaldehyde, 15g of terephthalonitrile and 1g of tetrabutylammonium hydroxide were dissolved in 2kg of mesitylene to prepare a solution. The dried resin was poured into the above solution, heated to 120℃ for reaction for 24h, filtered after the reaction to obtain the conjugated carbon-coated porous microsphere resin, poured into a 50% sulfuric acid solution, heated to 100℃ for reaction for 8h, and filtered to obtain the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin. 10g of ruthenium chloride was prepared into a 5% aqueous solution and heated to 60℃, the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin was poured into a metal salt solution and soaked for 8h, then the excess solution was filtered out and washed with methanol and toluene in turn, and the washed composite was dried at 100℃ for 12h to obtain a wet oxidation catalyst.

[0035] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 3.4mg / L and the removal rate was 96.6%.

[0036] Example 3 1kg of medium polar styrene porous microsphere resin with a particle size of 2mm was placed in a 100℃ blast drying oven for 12h for drying and standby use. 10g of biphenyl diformaldehyde, 15g of terephthalonitrile and 1g of tetrabutylammonium hydroxide were dissolved in 2kg of mesitylene to prepare a solution. The dried resin was poured into the above solution, heated to 120℃ for reaction for 24h, filtered after the reaction to obtain conjugated carbon-coated porous microsphere resin, poured into a 50% sulfuric acid solution, heated to 100℃ for reaction for 8h, and filtered to obtain sulfonic acid-modified conjugated carbon-coated porous microsphere resin. 10g of ruthenium chloride was prepared into a 5% aqueous solution and heated to 60℃, poured the sulfonic acid-modified conjugated carbon-coated porous microsphere resin into a metal salt solution and soaked for 8h, then filtered out the excess solution and washed with methanol and toluene in turn, and the washed composite was dried at 100℃ for 12h to obtain a wet oxidation catalyst.

[0037] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 2.6mg / L and the removal rate was 97.4%.

[0038] Example 4 1kg of medium polar styrene porous microsphere resin with a particle size of 2mm was placed in a 100℃ blast drying oven for 12h for drying and standby use. 10g of terephthalaldehyde, 15g of biphenyl diacetonitrile and 1g of tetrabutylammonium hydroxide were dissolved in 2kg of mesitylene to prepare a solution. The dried resin was poured into the above solution, heated to 120℃ for reaction for 24h, filtered after the reaction to obtain the conjugated carbon-coated porous microsphere resin, poured into a 50% sulfuric acid solution, heated to 100℃ for reaction for 8h, and filtered to obtain the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin. 10g of ruthenium chloride was prepared into a 5% aqueous solution and heated to 60℃, the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin was poured into a metal salt solution and soaked for 8h, then the excess solution was filtered out and washed with methanol and toluene in turn, and the washed composite was dried at 100℃ for 12h to obtain a wet oxidation catalyst.

[0039] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 2.9mg / L and the removal rate was 97.1%.

[0040] Comparative Example 1 1 kg of medium polar styrene porous microsphere resin with a particle size of 2 mm was placed in a 100°C forced air drying oven for 12 hours for drying and then poured directly into a 50% sulfuric acid solution without conjugated carbon coating and heated to 100°C for reaction for 8 hours, and filtered to obtain a sulfonic acid group-modified porous microsphere resin. 10 grams of ruthenium chloride was prepared into a 5% aqueous solution and heated to 60°C, and the sulfonic acid group-modified porous microsphere resin was poured into a metal salt solution and soaked for 8 hours, and then the excess solution was filtered out and washed with methanol and toluene in turn, and the washed composite was dried at 100°C for 12 hours to obtain a wet oxidation catalyst.

[0041] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 42.1mg / L and the removal rate was 57.9%.

[0042] Comparative Example 2 1 kg of medium-polar styrene porous microsphere resin with a particle size of 2 mm was placed in a 100°C forced air drying oven for 12 hours for drying for use. 10 grams of terephthalaldehyde, 15 grams of terephthalonitrile, and 1 gram of tetrabutylammonium hydroxide were dissolved in 2 kg of mesitylene to prepare a solution. The dried resin was poured into the above solution, and the temperature was raised to 120°C for reaction for 24 hours. After the reaction was completed, the conjugated carbon-coated porous microsphere resin was obtained by filtering. The resin was directly poured into a metal salt solution without sulfonation reaction and soaked for 8 hours. Then, the excess solution was filtered out and washed with methanol and toluene in turn. The washed composite was dried at 100°C for 12 hours to obtain a wet oxidation catalyst.

[0043] The catalyst was loaded into a wet reactor, 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 32.9mg / L and the removal rate was 67.1%.

[0044] Comparative Example 3 1 kg of medium-polar styrene porous microsphere resin with a particle size of 2 mm was placed in a 100°C forced air drying oven for 12 hours for drying for use, 10 grams of terephthalaldehyde, 15 grams of terephthalonitrile, and 1 gram of tetrabutylammonium hydroxide were dissolved in 2 kg of mesitylene to prepare a solution, the dried resin was poured into the above solution, the temperature was raised to 120°C and reacted for 24 hours, and after the reaction was completed, the conjugated carbon-coated porous microsphere resin was obtained by filtering, the above-obtained resin was poured into a 50% sulfuric acid solution, the temperature was raised to 100°C and reacted for 8 hours, and the sulfonic acid-modified conjugated carbon-coated porous microsphere resin was obtained by filtering.

[0045] The resin obtained in this step was directly loaded into a wet reactor. 2L of 100.0mg / L bisphenol A aqueous solution was poured into the reactor, and 2mL of hydrogen peroxide was added. The reaction was carried out at 150°C for 20min. After the reaction, the bisphenol A concentration was 53.2mg / L and the removal rate was 46.8%.

[0046] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a wet oxidation catalyst, characterized in that: The steps include: (1) Using styrene-based porous microsphere resin as raw material, multifunctional aldehyde small molecules and multifunctional cyano small molecules undergo Knoevenagel reaction by adsorption polymerization under the action of a catalyst, and a layer of conjugated carbon organic porous polymer is coated on the surface of the styrene-based porous microsphere resin to form a conjugated carbon-coated porous microsphere resin; (2) subjecting the conjugated carbon-coated porous microsphere resin to a sulfonation reaction to obtain a sulfonic acid group-modified conjugated carbon-coated porous microsphere resin; (3) The sulfonic acid group-modified conjugated carbon-coated porous microsphere resin is impregnated in a noble metal salt solution to form a resin-metal complex, which is then filtered, washed, and dried to obtain the wet oxidation catalyst.

2. The method for preparing a wet oxidation catalyst according to claim 1, characterized in that: The multifunctional aldehyde-based small molecule in step (1) is one or any combination of terephthalaldehyde, biphenyldicarboxaldehyde and trimesaldehyde.

3. The method for preparing a wet oxidation catalyst according to claim 1 or 2, characterized in that: The multifunctional cyano small molecule in step (1) is terephthalonitrile and / or biphenyl diacetonitrile.

4. The method for preparing a wet oxidation catalyst according to claim 1 or 2, characterized in that: The catalyst in step (1) is tetrabutylammonium hydroxide.

5. The method for preparing a wet oxidation catalyst according to claim 1 or 2, characterized in that: The reaction temperature of step (1) is 100-120°C.

6. The method for preparing a wet oxidation catalyst according to claim 1, characterized in that: The noble metal salt in step (3) is one or any combination of ruthenium chloride, iridium chloride, chloroauric acid, and platinum chloride.

7. The method for preparing a wet oxidation catalyst according to claim 1 or 6, characterized in that: The amount of the noble metal salt used in step (3) is 1-5% of the mass of the sulfonic acid group-modified conjugated carbon-coated porous microsphere resin.

8. The method for preparing a wet oxidation catalyst according to claim 1 or 6, characterized in that: The immersion temperature in step (3) is 60-80°C.

9. A wet oxidation catalyst, characterized in that: It is prepared by the method described in any one of claims 1 to 8.

10. Use of the wet oxidation catalyst according to claim 9 in degrading organic wastewater.

Citation Information

Patent Citations

  • Preparation method of catalytic wet oxidation catalyst and treatment method of organic wastewater

    CN103041811A

  • BCN catalyst for Knoevenagel condensation reaction and preparation and application thereof

    CN108371953A

  • Transition metal monatomic carbon-based catalyst and preparation method thereof

    CN116273121A

  • Wet oxidation catalyst as well as preparation method and application thereof

    CN116920853A

  • Conjugated polymer containing nitrile phenylene ethylene and its application

    CN1421469A

Cited By

  • Organic wastewater adsorbent as well as preparation method and application thereof

    CN120623565A

  • An organic wastewater adsorbent, a preparation method and application thereof

    CN120623565B